The Transport Properties of Quasi–One-Dimensional Ba3Co2O6(CO3)0.7 - Chen, Minnan; Wu, Jiangtao; Huang, Qing; Jiao, Jinlong; Dun, Zhiling; Wang, Guohua; Chen, Zhiwei; Lin, Gaoting; Rathinam, Vasudevan; Li, Cangjin; Pei, Yanzhong; Ye, Feng; et al. (Frontiers in Physics, 2021)
We have performed combined elastic neutron diffuse, electrical transport, specific heat and thermal conductivity measurements on the quasi-one-dimensional Ba3Co2O6(CO3)0.7 single crystal to characterize its transport properties. A modulated superstructure of polyatomic CO32– is formed, which not only interferes the electronic properties of this compound, but also reduces the thermal conductivity along the c-axis. Furthermore, a large magnetic entropy is observed to be contributed to the heat conduction. Our investigations reveal the influence of both structural and magnetic effects on its transport properties and suggest a theoretical improvement on the thermoelectric materials by building up superlattice with conducting ionic-group.